2018
DOI: 10.3389/fimmu.2018.01956
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 as a Modulator of Intestinal Inflammation Development and Progression

Abstract: Heme Oxygenase 1 (HMOX1) is an enzyme that catalyzes the reaction that degrades the heme group contained in several important proteins, such as hemoglobin, myoglobin, and cytochrome p450. The enzymatic reaction catalyzed by HMOX1 generates Fe2+, biliverdin and CO. It has been shown that HMOX1 activity and the by-product CO can downmodulate the damaging immune response in several models of intestinal inflammation as a result of pharmacological induction of HMOX1 expression and the administration of non-toxic am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 125 publications
0
51
1
3
Order By: Relevance
“…(3) PPIA, has been reported to be overexpressed in several types of human cancers including gastric cancer [51,55]. (4) HMOX1 is considered to be the main protein for cytoprotection against various cell stresses, and increased expression of this protein was observed in several types of cancers [56,57]. However, there are no differences in the levels of PPIA and HOMX1 between GC and controls in serum or in tissue in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…(3) PPIA, has been reported to be overexpressed in several types of human cancers including gastric cancer [51,55]. (4) HMOX1 is considered to be the main protein for cytoprotection against various cell stresses, and increased expression of this protein was observed in several types of cancers [56,57]. However, there are no differences in the levels of PPIA and HOMX1 between GC and controls in serum or in tissue in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…Similar to HSP70, HO-1 is the stress-inducible isoform of the three HO isoforms described to date, providing a critical protective mechanism in avian systems responsible for adaptation to oxidative, inflammatory and cytotoxic stress [136,137]. In most tissues HO-1 is expressed at a relatively low house-keeping level and it can be induced by various oxidative stress-related insults including haem, ultraviolet light, heavy metals, cytokines, hydrogen peroxide, nitric oxide (NO) and glutathione depletion [138,139]. The vital role of HO-1 in adaptation to stress has been shown in HO-1-deficient animal models characterised by atypical pro-inflammatory immune response with increased apoptosis [113].…”
Section: Heme Oxygenase-1mentioning
confidence: 99%
“…Experiments carried out in mice showed that enteric microbiota have the ability to regulate the activity of intestinal macrophages essential in killing pathogenic bacteria such as Salmonella enterica. This bactericidal effect was associated with an induction of HMOX-1/CO pathway by microbiota [49,73]. Moreover, the gut microbiota can produce CO due to the presence of enzymes with similar functions as HMOX-1.…”
Section: Parallelisms and Discrepancies In Co And H 2 S Effects And Tmentioning
confidence: 96%
“…Moreover, the gut microbiota can produce CO due to the presence of enzymes with similar functions as HMOX-1. In addition, CO can directly interact with heme-containing groups in some intestinal bacteria [73]. Importantly, in patients with ulcerative colitis, increased intestinal expression of HMOX-1 has been demonstrated [74].…”
Section: Parallelisms and Discrepancies In Co And H 2 S Effects And Tmentioning
confidence: 99%